2013
DOI: 10.1111/jace.12167
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Correlation between Dielectric Constant and Tunability in (Ba,Sr)TiO3MgOMg2SiO4 Composite Ceramics

Abstract: (Ba, Sr)TiO3–MgO–Mg2SiO4 composite ceramics were prepared by a solid‐state reaction method. The microstructures, microwave dielectric characteristics, and tunability of composite ceramics were investigated. An anomalous correlation between tunability and dielectric constant was observed: with the increase in Mg2SiO4 content and the decrease in MgO content, the dielectric constant of (Ba, Sr)TiO3–MgO–Mg2SiO4 composite ceramics decreases, but the tunability increases. The anomalous increased tunability is benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In our recent work, with the increase in Mg 2 TiO 4 from 7.5 to 50 wt%, the tunability of Ba 0.45 Sr 0.55 TiO 3 –Mg 2 TiO 4 and Ba 0.5 Sr 0.5 TiO 3 –Mg 2 TiO 4 under 2 kV/mm increased from 4.3% to 9.7% and from 8% to 14.2%, respectively . This unusual increased tunability can also be observed in the Ba 0.5 Sr 0.5 TiO 3 –Mg 2 SiO 4 –MgO and BST‐MgO system …”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…In our recent work, with the increase in Mg 2 TiO 4 from 7.5 to 50 wt%, the tunability of Ba 0.45 Sr 0.55 TiO 3 –Mg 2 TiO 4 and Ba 0.5 Sr 0.5 TiO 3 –Mg 2 TiO 4 under 2 kV/mm increased from 4.3% to 9.7% and from 8% to 14.2%, respectively . This unusual increased tunability can also be observed in the Ba 0.5 Sr 0.5 TiO 3 –Mg 2 SiO 4 –MgO and BST‐MgO system …”
Section: Resultssupporting
confidence: 52%
“…12 This unusual increased tunability can also be observed in the Ba 0.5 Sr 0.5 TiO 3 -Mg 2 SiO 4 -MgO and BST-MgO system. 6,10 Sherman et al have theoretically studied the dielectric properties of ferroelectric-dielectric composites. 16 In the spherical inclusion model, with a series of simplification, a formula which can describe the tunability was determined to be: n r = n f (1 + 0.2q).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, we observed that the abnormal increase in tunability also emerged in Ba 0.45 Sr 0.55 TiO 3 –MgO–Mg 2 TiO 4 system, which supports our speculation. We have investigated the dielectric tunable properties of BST–Mg 2 SiO 4 –MgO composite ceramics previously . Fixing dielectric content unchanged, with the increase in Mg 2 SiO 4 content and the decrease in MgO content, the tunability of composites increases.…”
Section: Introductionmentioning
confidence: 99%